Pathoanatomy of pertrochanteric fractures - a postmortem study - Bartoníček, Jan; Bartoška, Radek; Alt, Jan; Naňka, Ondřej; Tuček, Michal (Injury, 2023)
BACKGROUND: Recent pathoanatomic studies based on 3D CT reconstructions have questioned validity of AO/OTA classification because it does not reflect the reality and requires revision. These 3D CT studies, however, do not allow analysis of all details. Therefore, we have exploited the possibility to analyze the pathoanatomy of pertrochanteric fractures on postmortem specimens. MATERIAL AND METHODS: From the collection of the Institute of Anatomy, the authors obtained 16 specimens of hip joints of individuals who had sustained a pertrochanteric fracture and died within 30 days of the injury, with anteroposterior radiographs of the injured hip available in all of them. The number of major fragments and their shape, and the courses of the main fracture lines were studied. RESULTS: Three major fragments (a proximal head and neck fragment, a distal diaphyseal fragment and a posterior flat fragment), separated by three types of fracture lines (primary, secondary and tertiary lines) were identified. The primary line separated the proximal fragment (head and neck) from the distal diaphyseal fragment. The secondary fracture line separated the posterior flat fragment from the distal diaphyseal fragment. The tertiary fracture line split the posterior fragment into two parts. A key factor for fracture instability is the defect of the posterior cortex, which depends on the size and shape of the posterior fragment. Avulsion of the lesser trochanter and the adjacent cortex results in an unstable configuration of fracture lines on the medial side, while on the lateral side a large posterior fragment weakens the lateral trochanteric wall. CONCLUSION: In agreement with recent CT studies, the findings of this pathoanatomical study change, in a number of aspects, the traditional view of the pathoanatomy and classification of pertrochanteric fractures, and introduces the concept of three, instead of the traditional four, main fragments.
Keywords: Imaging, Three-Dimensional; Retrospective Studies; retrospektivní studie; Humans; Femoral Fractures; Femur; počítačová rentgenová tomografie; Tomography, X-Ray Computed; lidé; zobrazování trojrozměrné; fraktury kyčle; fraktury femuru; femur; Hip Fractures